3D-FEM computation and experimental study of eddy currents for characterization of surface cracks. Issue 5 (2nd October 2017) - Harzallah, Salaheddine; Chabaat, Mohamed
Abstract : Purpose: The purpose of this paper is to present a new approach for computing by measuring and testing related 3D Eddy currents. In the process, a magnetic vector is formulated from the theoretical setup and obtained results from relevant applications are checked for the consistency of the theory. Besides, cracks detection as well as its propagation is studied through the two parameters: SIF and J-integral. A simulation by a numerical approach using finite-element discretization of 3D governing equations is employed to detect damaged zones and cracks. This approach has been used in the aircraft industry to control cracks. Besides, it makes it possible to highlight the defects of parts while preserving the integrity of the controlled products. Obtained results are compared and agreed with those of other researchers. Design/methodology/approach: Finite-element discretization of 3D for solving problem in eddy current testing is presented in this paper. The main idea is the introduction of categorization for the shape reconstruction using the non-destructive testing by 3D-EC. The results are presented for a simple eddy current problem using the finite-element method as an experimental support. Findings: In this research work, results of the various cases of simulation have been obtained. From these results of various boxes of simulation, one can conclude that the calculation of the impedance in only one point is not enough to confirm the presence or the absence of a defect for materials. Then, this confirmation leads us to the calculation of the impedance along the plate. The detection of an external defect requires the energy of the sensor by high frequencies .The position of defect (internal, in the middle, external) has a large effect on the impedance. The use of this sensor type in industrial application is frequent because of its precision (minimal error) and its low costs. The major disadvantage of this type of sensor lies in the fact that it is unable to detect a defect. Originality/value: This paper fulfills an identified need to detect cracks in materials and eventually to study their propagation.